2013
DOI: 10.1186/1471-2474-14-79
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hand bone loss by digital X-ray radiogrammetry as a complement to clinical and radiographic assessment in early rheumatoid arthritis: results from the SWEFOT trial

Abstract: BackgroundTo investigate hand bone loss (HBL) measured by digital X-ray radiogrammetry (DXR) in patients with early rheumatoid arthritis (RA) receiving different treatment regimens, and to evaluate if DXR change rates during the first 12 months correlate with radiological damage after 24 months.MethodsFrom the total SWEFOT trial population, 159 patients had hand radiographs correctly timed and taken with same modality to be analyzed with DXR. All patients started treatment with methotrexate. After 3–4 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…A comparison of DXR and dual-energy X-ray absorptiometry (DXA) revealed that DXR appears to be more sensitive than DXA in detecting early bone loss in patients with RA [ 9 ]. Several studies have demonstrated a treatment effect of conventional and biologic disease-modifying antirheumatic drugs (bDMARDs) on BMD loss using DXR [ 4 , 12 17 ]; however, data are limited on identifying factors that are associated with BMD loss. Given the correlation of DXR–BMD with increased fracture risk and mortality [ 7 , 8 ], it would be beneficial to identify a reliable prognostic factor that is associated with hand BMD loss and treatment outcomes in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of DXR and dual-energy X-ray absorptiometry (DXA) revealed that DXR appears to be more sensitive than DXA in detecting early bone loss in patients with RA [ 9 ]. Several studies have demonstrated a treatment effect of conventional and biologic disease-modifying antirheumatic drugs (bDMARDs) on BMD loss using DXR [ 4 , 12 17 ]; however, data are limited on identifying factors that are associated with BMD loss. Given the correlation of DXR–BMD with increased fracture risk and mortality [ 7 , 8 ], it would be beneficial to identify a reliable prognostic factor that is associated with hand BMD loss and treatment outcomes in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Compared with CR, which reportedly only detects damage if the reduction in bone density is more than 35%, 16 17 31 digital BMD measuring has a higher sensitivity. This may be important in the clinic when DMARDs may halt or slow down progression to a point where the CR method is not sensitive enough to measure a difference.…”
Section: Discussionmentioning
confidence: 99%
“…The interclass correlation coefficient was 0.94 and the smallest detectable difference (SDD) in SHS was 5.8 units. 16 …”
Section: Evaluation Criteriamentioning
confidence: 99%
“…Bone loss detected by this method has repeatedly been shown to predict radiographic joint progression in early RA. [85][86][87][88]. However, the majority of previous studies investigated 12-months changes in DXR-BMD, and after this time, DXR-evaluation of joint damage was not superior to conventional radiography for prediction of further radiologic progression Except QCT, which measures bone mineral mass per volume, the other methods measure per projected area.…”
Section: Digital X-ray Radiogrammetrymentioning
confidence: 99%